A CXCR4 receptor agonist strongly stimulates axonal regeneration after damage. Issue 12 (14th November 2019) - Zanetti, Giulia; Negro, Samuele; Megighian, Aram; Mattarei, Andrea; Lista, Florigio; Fillo, Silvia; Rigoni, Michela; Pirazzini, Marco; Montecucco, Cesare
Abstract: Objective: To test whether the signaling axis CXCL12α‐CXCR4 is activated upon crush/cut of the sciatic nerve and to test the activity of NUCC‐390, a new CXCR4 agonist, in promoting nerve recovery from damage. Methods: The sciatic nerve was either crushed or cut. Expression and localization of CXCL12α and CXCR4 were evaluated by imaging with specific antibodies. Their functional involvement in nerve regeneration was determined by antibody‐neutralization of CXCL12α, and by the CXCR4 specific antagonist AMD3100, using as quantitative read‐out the compound muscle action potential (CMAP). NUCC‐390 activity on nerve regeneration was determined by imaging and CMAP recordings. Results: CXCR4 is expressed at the injury site within the axonal compartment, whilst its ligand CXCL12α is expressed in Schwann cells. The CXCL12α‐CXCR4 axis is involved in the recovery of neurotransmission of the injured nerve. More importantly, the small molecule NUCC‐390 is a strong promoter of the functional and anatomical recovery of the nerve, by acting very similarly to CXCL12α. This pharmacological action is due to the capability of NUCC‐390 to foster elongation of motor neuron axons both in vitro and in vivo . Interpretation: Imaging and electrophysiological data provide novel and compelling evidence that the CXCL12α‐CXCR4 axis is involved in sciatic nerve repair after crush/cut. This makes NUCC‐390 a strong candidate molecule to stimulate nerve repair by promoting axonal elongation. We propose this molecule to be tested in other models of neuronal damage, to lay the basis for clinical trials on the efficacy of NUCC‐390 in peripheral nerve repair in humans.